Resiliensi Anak yang Berkonflik Dengan Hukum: Refleksi Implementasi UU. No.11 Tahun 2012 Mengenai Proses Diversi - nailatin fauziyah (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
Settlement of child criminal cases using the restorative justice approach and diversion in accordance with Law No. 11 of 2012 is an important breakthrough in the development of criminal law processes in Indonesia. At the conceptual level, the implementation of the process takes into consideration the fulfillment of children's rights and has a concern for the child's future. To achieve the future the child must have the resilience to deal with difficult situations throughout his life journey. Likewise, children who are in conflict with the law, on the other hand they are perpetrators of crime and on the other hand they are victims of the surrounding social system. The results of this study indicate that Children in conflict with the law (ABH) who are resilient tend to get support from various parties so that they can get through difficult situations and face the future with confidence, but conversely with ABH who are not resilient. The results of this study are important notes to reflect back the implementation of Law No.11/2012 on restorative justice and diversion, because the diversion process undertaken by ABH does not differentiate their resilience levels. It is the strength of the protective factor that affects the differences in the resilience of ABH who undergo legal proceedings through diversion.